Diurnal Changes of Heart Rate and Sympathovagal Activity for Temporal Patterns of Transient Ischemic Episodes in 24-Hour Electrocardiograms. (22nd March 2007) - Smrdel Smrdel, A. A.; Jager Jager, F. F.
Abstract : We test the hypothesis that different temporal patterns of transient ST segment changes compatible with ischemia (ischemic episodes) are a result of different physiologic mechanisms responsible for ischemia. We tested the hypothesis using records of the Long-Term ST Database. Each record was divided into three intervals of records: morning, day, and night intervals; and was inserted into one of three sets according to the temporal pattern of ischemia: salvo, periodic, and sporadic pattern. We derived time- and frequency-domain parameters of the heart rate time series in selected intervals in the neighborhood of ischemic episodes. We used the adaptive autoregressive method with a recursive least-square algorithm for consistent spectral tracking of heart rate time series and to study frequency-domain sympathovagal behavior during ischemia. The results support the hypothesis that there are at least two distinct populations, which differ according to mechanisms and temporal patterns of ischemia.